Efficiency and precision of microRNA biogenesis modes in plants - Moro, Belén (2018)
Many evolutionarily conserved microRNAs (miRNAs) in plants regulate transcription factors with key functions in development. Hence, mutations in the core components of the miRNA biogenesis machinery cause strong growth defects. An essential aspect of miRNA biogenesis is the precise excision of the small RNA from its precursor. In plants, miRNA precursors are largely variable in size and shape and can be processed by different modes. Here, we optimized an approach to detect processing intermediates during miRNA biogenesis. We characterized a miRNA whose processing is triggered by a terminal branched loop. Plant miRNA processing can be initiated by internal bubbles, small terminal loops or branched loops followed by dsRNA segments of 15-17 bp. Interestingly, precision and efficiency vary with the processing modes. Despite the various potential structural determinants present in a single a miRNA precursor, DCL1 is mostly guided by a predominant structural region in each precursor in wildtype plants. However, our studies in fiery1, hyl1 and se mutants revealed the existence of cleavage signatures consistent with the recognition of alternative processing determinants. The results provide a general view of the mechanisms underlying the specificity of miRNA biogenesis in plants.